التقابل اللغوي بين اللغة العربية و الإنجليزية - Zulfikri Muhammad (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2018)
Although Arabic and English comes from a different clumps, Arabic is included in the Semitic language family and still related to the Hebrew language, while English is included in Germanic or better known as Anglo Saxons, but there are also points of similarity between Arabic and English. The comparison between Arabic and English is more famous in the world and interested to discuss in order to facilitate Language Learning. In this article the author discusses the similarities and differences between Arabic and English in terms of pattern or structure of sentence formation